KOMUNIKASI DAKWAH DALAM KESENIAN NASYID - Yanti, Fitri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This paper deals with Islamic psalm ( nasyid ) which contain moral messages, past memories, stories of the prophets, and call for Islamic preaching and spirit to build nation and state.  It serves a lot of functions. Nasyid can serve as a method of preaching that is entertaining and conveying messages to Muslim community. With nasyid , messages of preaching conveyed are not boring to the targets of preaching, but they feel attracted to it. Therefore, it can be effective to call them to perform the good and to prevent the evil.